Development and profiling of mGlu7 NAMs with a range of saturable inhibition of agonist responses in vitro. (15th October 2022) - Reed, Carson W.; Rodriguez, Alice L.; Kalbfleisch, Jacob J.; Seto, Mabel; Jenkins, Matthew T.; Blobaum, Anna L.; Chang, Sichen; Lindsley, Craig W.; Niswender, Colleen M.
Graphical abstract: Abstract: We describe here a series of metabotropic glutamate receptor 7 (mGlu7 ) negative allosteric modulators (NAMs) with a saturable range of activity in inhibiting responses to an orthosteric agonist in two distinct in vitro pharmacological assays. The range of inhibition among compounds in this scaffold provides highly structurally related ligands with differential degrees of receptor blockade that can be used to understand inhibitory efficacy profiles in native tissue or in vivo .